Globalization and counterdevelopment: The importance of new narratives. Issue 4 (12th November 2020) - Bidegain, Ana Maria
Abstract: The article is a personal recount of living under the called neoliberal regime installed in the post‐Cold War in the region. Written from the perspective of a Latin American woman in the betweenness of the North and the South. Focusing on capitalism history shows how counterdevelopment has been the other face of globalization. The social protests in the whole continent request the respect of human dignity recovering an inclusive collective narrative and social justice caring of our common home, to build a more profound democracy and a more just world.